2018
DOI: 10.1097/jdn.0000000000000385
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner Student Knowledge and Attitudes Toward Skin Cancer Assessments

Abstract: Early detection and treatment of skin cancer is directly related to patient outcomes. However, little is known about how prepared nurse practitioner students are to assess and manage skin lesions. Therefore, the purpose of this study was to assess nurse practitioner student knowledge to determine how well they are being prepared to perform skin cancer assessments. This exploratory, descriptive study surveyed 20 nurse practitioner students about their knowledge, attitudes, and confidence in identifying differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…Yet, few studies have focused on preparing NP students for detecting cancerous skin lesions (Woodmansee et al, 2018). A recent descriptive study of 20 NP students from various specialty concentrations revealed insufficient knowledge of skin cancer (mean subscale score 6.40 out of possible 13.00 points) and of lesion identification (mean subscale score 9.65 out of possible 20.00 points) (Woodmansee et al, 2018). Further, 70% of the NP student participants reported that they had not received enough dermatology training to feel prepared for practice, and 90% were not confident to perform skin assessments.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, few studies have focused on preparing NP students for detecting cancerous skin lesions (Woodmansee et al, 2018). A recent descriptive study of 20 NP students from various specialty concentrations revealed insufficient knowledge of skin cancer (mean subscale score 6.40 out of possible 13.00 points) and of lesion identification (mean subscale score 9.65 out of possible 20.00 points) (Woodmansee et al, 2018). Further, 70% of the NP student participants reported that they had not received enough dermatology training to feel prepared for practice, and 90% were not confident to perform skin assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Further, 70% of the NP student participants reported that they had not received enough dermatology training to feel prepared for practice, and 90% were not confident to perform skin assessments. The majority (90%) reported feeling afraid that they would miss detecting a patient's skin cancer (Woodmansee et al, 2018). Lack of knowledge about skin cancer assessments has also been found to persist after graduation, and a survey of 272 practicing NPs found that 84.2% desired for more education on melanoma (Roebuck et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure nurses and nurse practitioners are prepared to improve skin cancer awareness and outcomes, universities should incorporate more skin cancer education into undergraduate and graduate curricula (Woodmansee et al, 2018). In undergraduate and graduate nursing programs, education regarding skin assessments, recognition of atypical lesions, and prevention strategies should be emphasized (Shue-McGuffin & Powers, 2022).…”
Section: Additional Recommendationsmentioning
confidence: 99%